2015
DOI: 10.1177/2333721415603193
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self-Rated Masticatory Ability and Independent Life in Community-Dwelling Older Adults

Abstract: Objective: The aim of the present study was to elucidate the influence of self-rated masticatory ability on independent living in community-dwelling older adults. Method: A total of 1,377 subjects aged 65 and over who lived in Kumamoto City, Japan were participated in a survey to investigate critical factors for self-reliance in older adults. In this study, we defined independent life in older adults as self-perceived adequate health without long-term care certification. Logistic regression analysis was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In Japan, the rate of aging exceeded 21% in the year 2007, which is the fastest rate of aging in the world, and the proportion of the elderly continues to increase in this super-aged society [1]. Consequently, the relationship between oral health and general health has been discussed by previous studies , with the extension of healthy life expectancy and the reduction of health disparities as the fundamental objectives [2][3][4][5]. Oral health is important for maintaining the pleasure of eating and speaking and it greatly contributes to the improvement of the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the rate of aging exceeded 21% in the year 2007, which is the fastest rate of aging in the world, and the proportion of the elderly continues to increase in this super-aged society [1]. Consequently, the relationship between oral health and general health has been discussed by previous studies , with the extension of healthy life expectancy and the reduction of health disparities as the fundamental objectives [2][3][4][5]. Oral health is important for maintaining the pleasure of eating and speaking and it greatly contributes to the improvement of the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that the physical pre-frailty status of participants was significantly associated with masticatory performance [ 23 ]. Furthermore, Hironaka et al revealed that masticatory ability was associated with diet variety [ 25 ]. Consequently, an increase in weight and BMI after intervention might be considered the result of an improvement in oral function.…”
Section: Discussionmentioning
confidence: 99%